Design and Synthesis of new Naproxen Analogues as Potential Anti-inflammatory Agents - Noor H. Nasser; Nethal H. Hammud; Samer A. Hasan; Abbas Hamid Abdalsadh; Ahmed kareem Hussein (College of Pharmacy / Mustansiriyah University, 2018)
4-aminobenzenesulfonamide derivatives were linked to α-carbon of naproxen a non-selective non-steroidal anti-inflammatory drug (NSAID) to increase its size, so; increase its selectivity toward COX-2 enzyme, rather than COX-1 enzyme, that lead to reduce gastrointestinal side effects of this drug. The chemical structures of the synthesized compounds and their intermediates were confirmed and characterized using elemental microanalysis (CHN), FTIR, and other physicochemical properties like melting points, Rf values.